Association of trajectories of depressive symptoms with vascular risk, cognitive function and adverse brain outcomes: The Whitehall II MRI sub-study - Demnitz, N; Anaturk, M; Allan, CL; Filippini, N; Griffanti, L; Mackay, CE; Mahmood, A; Sexton, C; Suri, S; Topiwala, A; Zsoldos, E; Kivimäki, M; et al. (Elsevier, 2020)
Background: Trajectories of depressive symptoms over the lifespan vary between people, but it is unclear whether these differences exhibit distinct characteristics in brain structure and function.